Implementing Blended Learning Model in Teaching English in the Era of the Industrial Revolution 4.0" - Ninsiana, Widhiya; Yulianingsih, Lilik (Journal of Ecohumanism, 2025)
This study aims to: (1) produce a Moodle-based English e-learning product that is feasible in improving speaking skills in English learning for SMP and SMA in Metro City (2) to find out how effective Moodle-based e-learning is on speaking skills in language learning English, junior high and high school students in Metro City, Lampung. The type of research in this study applies the R&D model through the following three steps: planning, design, and development. The subjects in this study were junior high and high school students. Data collection techniques used was interviews, questionnaires, and tests. Based on the results of data analysis and discussion, it can be concluded that Moodle-based e-learning products can be an alternative learning to which provide students with facilities where they can lean and hone their speaking skills as the learning outcomes, the results of research and development of various Moodle based e-learning products improve students’ speaking skills in learning English for both senior and junior high school students.